Optimizing soft skill development in vocational high schools by utilizing artificial intelligence - Amam, Asep; Effendi, Adang; Fatimah, Ai Tusi; Manjilah, Rifa Rifatul; Rahman , Muhammad Naufal (Galuh International Journal of Community Service and Development, 2024)
This community service initiative was aimed at enhancing the soft skills of students at the State Vocational High School (SMKN) 1 Rajadesa, Indonesia by using artificial intelligence. The program was attended by 27 students specializing in accounting. The mentoring process began with coordinating with partners to determine the timing and location of the research, prepare activity guidebooks, and create assessment tools to measure the improvement in soft skills before and after the mentoring. The mentoring included introducing ChatGPT as an artificial intelligence tool for solving mathematical problems. The soft skills developed for students included critical thinking, creativity, communication, cooperation, adaptability, problem-solving, problem identification, and independent learning. Based on the pre-and post-mentoring assessments, 67% of students had high soft skills, 29% were at a moderate level, and 4% were at a low level. On average, students could use ChatGPT to comprehend concepts and understand mathematical problem-solving steps. This community service positively impacted mathematics students at SMK Negeri 1 Rajadesa for further utilization of artificial intelligence by students in mathematics learning. A follow-up assessment to track the long-term effects of the program on the students’ performances, career prospects, and overall well-being needs to be done.